2010
DOI: 10.1016/j.drugalcdep.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood education inequality and drinking behavior

Abstract: Background The neighborhood distribution of education (education inequality) may influence substance use among neighborhood residents. Methods Using data from the New York Social Environment Study (conducted in 2005; n=4,000), we examined the associations of neighborhood education inequality (measured using Gini coefficients of education) with alcohol use prevalence and levels of alcohol consumption among alcohol users. Analyses were adjusted for neighborhood education level, income level, and income inequal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…To compare the zero drinking and risky drinking hurdle models to a commonly used longitudinal Poisson regression model (e.g., Le and Galea, 2010; Bandyopadhyay et al, 2011; Walley et al, 2012) three statistics were calculated. The Akaike information criteria (AIC) and Bayesian information criteria (BIC) were used to compare non-nested models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the zero drinking and risky drinking hurdle models to a commonly used longitudinal Poisson regression model (e.g., Le and Galea, 2010; Bandyopadhyay et al, 2011; Walley et al, 2012) three statistics were calculated. The Akaike information criteria (AIC) and Bayesian information criteria (BIC) were used to compare non-nested models.…”
Section: Methodsmentioning
confidence: 99%
“…These outcomes are usually analyzed using generalized linear models (GML) but zero-inflated Poisson or binomial (ZIP, ZIB) regression may be used to model consumption if data violate the assumptions of GLMs. There have been several applications of such zero inflated models in the substance use literature (Le and Galea, 2010; Hu et al, 2011; Meszaros et al, 2011; DeSantis et al, 2011; Fielder et al, 2012; Peeters et al, 2012; Walley et al, 2012). However, the statistical assumption of zero inflated models is that zero drinking arises from a set of patients who have zero risk of drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting vulnerability to alcoholism provides a point of departure in the creation of prevention and intervention initiatives, and it requires a longitudinal examination of behavioral, socioeconomic, and environmental factors associated with the development of these problems (Chermack & Giancola, ; Tarter & Vanyukov, ). Previous research has identified how individual‐level and neighborhood‐level factors jointly influence alcohol use ( Buu et al, ; Hill & Angel, ; Lê, Ahern, & Galea, ; Mulia, Zemore, & Greenfield, ; Stockdale et al, ); however, identifying precursors of alcoholism within a longitudinal, ecological framework has yet to be established despite its practical and theoretical implications for understanding how various factors shape this problematic outcome.…”
Section: Neighborhood Context and Alcohol Usementioning
confidence: 99%
“…Studies linking census‐based assessments of neighborhood context to alcohol‐related outcomes are not unequivocal. Although some studies have found that factors associated with lower neighborhood SES, such as percentage of individuals living below the poverty line, neighborhood instability, and lowered neighborhood educational attainment, are associated with increased alcohol use (Buu et al, ; Hill & Angel, ; Jones‐Webb, Snowden, Herd, Short, & Hannan, ; Lê et al, ; Mulia et al, ; Stockdale et al, ), other studies have not supported this association (Brenner, Bauermeister, & Zimmerman, ; Galea, Ahern, Tracy, Rudenstine, & Vlahov, ; Gardner, Barajas, & Brooks‐Gunn, ; Snedker, Herting, & Walton, ; Trim & Chassin, ). These incongruent findings may exist for several reasons, including the age of the population under examination, the racial/ethnic composition of the sample, and the use of different indices of neighborhood SES.…”
Section: Neighborhood Context and Alcohol Usementioning
confidence: 99%
“…level, the more probability of adequate nutrition -and hence, less chance for presenting obesity and its comorbidities-due to the fact that these individuals are often more aware of the importance of nutritional habits and the practice of regular exercise [5,6]. On this regard, it has been established [12][13][14] that those with more years of education are less likely to smoke, drink heavily, or to be overweighed or obese. Similarly, the better educated subjects are more likely to exercise and use preventive care procedures such as vaccines, mammograms, Papanicolau tests and colonoscopies.…”
Section: Background and Objectivementioning
confidence: 99%